1985
DOI: 10.1007/bf00501208
|View full text |Cite
|
Sign up to set email alerts
|

Cooling-induced supersensitivity to acetylcholine in the isolated airway smooth muscle of the rat

Abstract: Isolated tracheal and bronchial strip-chain preparations of the rat were used to study the effect of temperature on electrically or acetylcholine-induced contraction. The preparations were suspended in the organ bath containing Krebs bicarbonate solution for isometric tension recording. A decrease of bath temperature from 37 degrees C to 20 degrees C (cooling) had no effect on basal tone but augmented the contractile responses of the trachea and bronchus caused by stimulation of intramural cholinergic nerves (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

1986
1986
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…(19). Although we did not investigate the effect of diabetes on the binding characteristics of muscarinic receptors in rat trachea, the increased contractilities to ACh and KC1 in diabetic tracheas without any change in the sensitivity (pD 2 ) indicate that the hyper-responsiveness may be dependent to the alterations in (22,23,24). It has been shown that oxidative stress is responsible for the increased contractile responsiveness of diabetic vasculature by increasing diacylglycerol -protein kinase C (DAC-PKC) activity which stimulates IP 3 induced Ca +2 release from intracellular organelles leading to intracellular Ca +2 accumulation in diabetes mellitus (25,26).…”
Section: Discussionmentioning
confidence: 92%
“…(19). Although we did not investigate the effect of diabetes on the binding characteristics of muscarinic receptors in rat trachea, the increased contractilities to ACh and KC1 in diabetic tracheas without any change in the sensitivity (pD 2 ) indicate that the hyper-responsiveness may be dependent to the alterations in (22,23,24). It has been shown that oxidative stress is responsible for the increased contractile responsiveness of diabetic vasculature by increasing diacylglycerol -protein kinase C (DAC-PKC) activity which stimulates IP 3 induced Ca +2 release from intracellular organelles leading to intracellular Ca +2 accumulation in diabetes mellitus (25,26).…”
Section: Discussionmentioning
confidence: 92%
“…man, dog, guinea-pig and rat has been demonstrated to potentiate contractile responses to histamine, acetylcholine (ACh) or methacholine, etc. (Souhrada & Souhrada, 1981;Murlas et al, 1982;Tran et al, 1982;Ishii & Shimo, 1985). In the present study, the effect of antigen challenge on cold-induced responses in rat isolated tracheal segments was investigated.…”
Section: Introductionmentioning
confidence: 80%
“…The results showed that cooling of the airways can enhance or reduce agonistinduced contractions. Cholinergically induced contractility is enhanced in humans [1,2], rabbits [3], hamsters [4], rats [5], and dogs [6]. On the other hand, cholinergically induced contractility is reduced or unchanged in the guinea pig, depending on the agonist used.…”
Section: Introductionmentioning
confidence: 99%
“…Ishii and Shimo [5] reported that the increased contractions of the rat trachea to EFS are due to an enhanced sensitivity of the cholinoceptors to the neurotransmitter (acetylcholine). This was based on the fact that acetylcholine-induced (with or without cholinesterase inhibition) contractions of the rat trachea were similarly enhanced by cooling.…”
Section: Effect Of Cooling On the Efs Responses Excitatorymentioning
confidence: 99%
See 1 more Smart Citation